THE EFFECT OF SUBSURFACE GROUND CONDITION ON THE PERFORMANCES OF MICROTUNNELLING BORING MACHINE (MTBM) - AHMRAN, MUHAMMAD SHAFIQ AIMAN (2020)
The performance of microtunnelling boring machine (MTBM) is represented by certain parameters such as advancement rate, efficiency in controlling line and level, less ground surface disturbance and jacking force. These parameters are closely related to subsoil properties which are types of soils, SPT ‘N’ value and ground water table. This research aims to investigate how these factors relate to each other. The chosen project comprising the installation of 1300mm diameter of sewerage reinforced jacking pipe (RCJP) using pipe jacking and microtunnelling method at Jalan Pengkalan Perindustrian, Ipoh Perak.